Sepsis Team Organizational Model to Decrease Mortality for Intra-Abdominal Infections: Is Antibiotic Stewardship Enough? - Carlo Vallicelli; Giorgia Santandrea; Massimo Sartelli; Federico Coccolini; Luca Ansaloni; Vanni Agnoletti; Francesca Bravi; Fausto Catena (MDPI AG, 2022)
Introduction. Sepsis is an overwhelming reaction to infection with significant morbidity, requiring urgent interventions in order to improve outcomes. The 2016 Sepsis-3 guidelines modified the previous definitions of sepsis and septic shock, and proposed some specific diagnostic and therapeutic measures to define the use of fluid resuscitation and antibiotics. However, some open issues still exist. Methods. A literature research was performed on PubMed and Cochrane using the terms "sepsis" AND "intra-abdominal infections" AND ("antibiotic therapy" OR "antibiotic treatment"). The inclusion criteria were management of intra-abdominal infection (IAI) and effects of antibiotic stewardships programs (ASP) on the outcome of the patients. Discussion. Sepsis-3 definitions represent an added value in the understanding of sepsis mechanisms and in the management of the disease. However, some questions are still open, such as the need for an early identification of sepsis. Sepsis management in the context of IAI is particularly challenging and a prompt diagnosis is essential in order to perform a quick treatment (source control and antibiotic treatment). Antibiotic empirical therapy should be based on the kind of infection (community or hospital acquired), local resistances, and patient's characteristic and comorbidities, and should be adjusted or de-escalated as soon as microbiological information is available. Antibiotic Stewardship Programs (ASP) have demonstrated to improve antimicrobial utilization with reduction of infections, emergence of multi-drug resistant bacteria, and costs. Surgeons should not be alone in the management of IAI but ideally inserted in a sepsis team together with anaesthesiologists, medical physicians, pharmacists, and infectious diseases specialists, meeting periodically to reassess the response to the treatment. Conclusion. The cornerstones of sepsis management are accurate diagnosis, early resuscitation, effective source control, and timely initiation of appropriate antimicrobial therapy. Current evidence shows that optimizing antibiotic use across surgical specialities is imperative to improve outcomes. Ideally every hospital and every emergency surgery department should aim to provide a sepsis team in order to manage IAI.